Strength and nature of hydrogen bonding interactions in mono-and di-hydrated formamide complexes - Angelina, Emilio Luis (2011)
Fil: Angelina, Emilio Luis. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.